PERAN KOALISI PEMUDA HIJAU (KOPHI) KALIMANTAN TIMUR DALAM PENGURANGAN PENGGUNAAN KANTONG PLASTIK DI KOTA SAMARINDA - Dewi Risnawati; Syahrani Syahrani; Enos Paselle (Magister Administrasi Publik FISIP Universitas Mulawarman, 2021)
This study aims to determine the role of KOPHI and inhibiting factors in Reducing the Use of Plastic Bags in Samarinda City. This research was conducted in Samarinda City. The role of KOPHI is focused on the activities carried out by Kophi through the focus of research, namely: (1) Conducting Plastic Bag Reduction Campaigns (less plastic), (2) Carrying out Educational Activities for Wisely Using Plastic, (3) Becoming a Media and Facilitator for Youth Generation in Creating a Real and Sustainable Green Movement, (4) Inhibiting factors implementing the Youth's Role in Reducing the Use of Plastic Bags in Samarinda City. The results of this research is shows the role of KOPHI in Reducing the Use of Plastic Bags in Samarinda City shows that the role of KOPHI has been going well, this is because KOPHI can be able to bridge and become a facilitator between young people and other communities in an effort to reduce the use of plastic bags in Samarinda City. This is evidenced by the fact that the reduction of youth and the community in using disposable plastic in Samarinda City and switching to using shopping bags (totebag). Inhibiting factors in reducing the use of plastic bags include, habitual factors, assessment factors because they have thoughts that are not yet open and difficult to predict, and there are other options besides participating in activities.Keyword : Kophi, Role, Trash, Youth